Aristotle eaudiobook On poetry. - Aristotle (Mission Audio, 2010)
Aristotle's Poetics is the earliest-surviving work of dramatic theory and the first fully intact philosophical treatise to focus on literary theory. In it, the respected Greek sage offers an account of what he calls "poetry" (which the Greeks understood to literally mean "making"), examining its "first principles" and identifying its genres and basic elements, including what he terms drama-comedy, tragedy, and the satyr play-as well as lyric poetry, epic poetry, and iambic pentameter, which he always associates with wit.